Relationship between the alignment of a non-mydriatic fundus camera, anterior chamber depth and axial length - Guo, Yin; Zhang, Yaqin; Jonas, Jost B. (Yan ke xue bao, 2012)
Purpose:To evaluate the relationship between the position of the focal adjustment knob of a fundus camera and refractive error and biometric data as measured in the same eye.Methods:Normal eyes of patients presenting to clinics at the Beijing Tongren Hospital were examined with a non-mydriatic fundus camera.The position on the focal scale of a knob adjusting the distance between the camera lens and film plane,used to adjust focus the image of the patients fundus relative to the refractive power of the eye,was recorded in degrees.Ocular biometry and refractometry were performed on the same eyes.Results:The study included 136 subjects with a mean age of 36.5 ±19.6 years and a mean refractive error of-1.31 ±2.77 diopters.In univariate analysis,the position of the adjustment knob was significantly associated with refractive error.(P < 0.001;correlation coefficient r=-0.77),axial length.(P<0.001;r=0.65) and anterior chamber depth (P<0.001;r=0.48).After adjustment for age,anterior chamber depth decreased by 0.01 mm(95% confidence interval:0.003,0.017) for change per degree in the position of the adjustment knob.Conclusion:A fundus camera can be used to estimate anterior chamber depth,axial length and refractive error.In a screening setting,a fundus camera operated by a technician may be helpful to detect a shallow anterior chamber and evaluate a potential risk factor for primary angle closure.